COMPARISON OF NEEDLE ASPIRATIONS AND INCISION & DRAINAGE OF BREAST ABSCESS - Sajid Rehman Randhawa; Muhammad Akram; Haseeb Akram; Muhammad Sajid (Journal of University Medical & Dental College, 2019)
OBJECTIVE: The objective of this study was to compare the success of needle aspirations and incision and drainage of breast abscess.STUDY DESIGN: It is a Randomized Control TrialSETTING: Study was conducted in Surgical Department of Allied Hospital FaisalabadDURATION OF STUDY: Six months (From: 01-03-2017 to 31-08-2017).METHODOLOGY: After approval of study from ethical review committee and informed consent the patients fulﬁlling the inclusion criteria were subjected to complete history and clinical examination in addition to baseline investigations. Patients divided in two groups by simple random sampling. Group A underwent multiple aspirations under ASM with 18 gauge needle under cover of oral Co- amoxiclav 1g B.D for maximum of 14 days. 2% lignocaine HCl solution was used as local anaesthetic. Group B underwent incision and drainage under general anaesthesia. Each patient was given a shot of antibiotic at the time of induction of anesthesia. Post-operatively patient were kept NPO for 6 hrs and treated by IV ﬂuids, antibiotics and analgesics, and discharged when started orally.All procedures were performed by Assistant Professors or Senior Registrars or Senior Post graduate Residents. Post-procedure follow up was done once weekly for 2 weeks and then patients were examined for success rate {absence of symptoms (pain, swelling, redness, fever, tenderness) in case of multiple aspirations under antibiotic cover and complete healing of wound in case of incision and drainage} on the 20th post-operative day.RESULTS: In this study, mean age was calculated as 29.74+7.636 in group A and 31.40+9.775 in group B. Comparison of success rates was done showing procedural success 97.1% (n=34) in group A and 82.9% (n=29) in group B. P-value calculated (0.046) which also showed a signiﬁcant diﬀerence.CONCLUSION: We concluded that the frequency of early success rate of multiple aspirations under antibiotic cover in terms of early healing of breast abscess is signiﬁcantly higher as compared to incision and drainage.